Body Weight Performance of Ongole Grade Cattle at BPTU-HPT Sembawa Banyuasin South Sumatra - Mochammad Hafizh Zulkarnaen; Heni Indrijani; Muhamad Fatah Wiyatna; Asep Anang (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
Ongole Grade cattle development continues to be carried out, because it has a uniform physical form and genetic composition, as well as the ability to adapt well to environmental constraints. Selection of beef cattle can be done by considering the quantitative characteristics of beef cattle, so that beef cattle with the best performance can be obtained. The aim of the study was to analyze the performance of birth weight, weaning weight (205 days), and yearling weight in Ongole Grade cattle at BPTU-HPT Sembawa from 2014 – 2021 which is influenced by sex and parity. The total records used were 1,125 weight records consisting of 424 birth weight records, 360 weaning weight records, and 341 yearling weight records, which consisted of 9 sires, 178 dams, 199 male calves and 225 female calves. Records were analyzed using the General Linear Model (GLM) and Duncan Multiple Range Test to determine the effect of sex and parity using SAS 9.0 software. The results showed that the performance of birth, weaning, and yearling weight were significantly affected (P<0.05) by sex and parity. Correction of body weight performance of Ongole Crossbreed cattle should be carried out before analyzing genetic parameters to reduce possible bias in the selection results.